Analise econômica da injeção de água em campos maduros na região da bacia potiguar utilizando um modelo bidimensional - Albuquerque, Talles André Morais (Universidade Federal Rural do Semi-Árido, 2018)
The Rio Grande do Norte state has been nationally prominent for several decades as one of the major petroleum producers. In oil producing regions, the technical and economic viability of a reservoir can be defined from the recovery method. These methods can be classified into natural recovery, in which the proper and energy present in the reservoir stone is sufficient for the production of fluids, conventional through the injection of water or gas and special which comprise the thermal, chemical and recoverable hydrocarbons. During the field recovery analysis step, one of the most important tools to perform the analysis is the numerical simulation. In this way, this work compromises a numeric simulation study of petroleum recovery through the injection of water in onshore fields of the Bacia Potiguar region. Four reservoirs with permeability, porosity, fluid saturation, viscosity and injection flow parameters were analyzed. These studies included the design and grid refining, variation of viscosity and flow of the injected water, a sensitivity analysis of the Recovery Factor in function of reservoir parameters and, finally, a financial feasibility study through the analysis of the VPL and TIR. From the simulations carried out, the results showed improvements in the Recovery Factor with the increase of the injection rate and the viscosity of the injected water for all cases analyzed. The results of the sensitivity analysis indicated that the most relevant parameters in the improvement of the Recovery Factor were porosity of the formation and initial petroleum saturation. It was analyzed how the injection projects would behave financially through the study of the VPL e TIR, and it was verified that for the analyzed conditions the injection projects would not present financial viability.
Monografia
Keywords: Fator de recuperação; Simulação numérica; Recuperação secundária; Recovery factor, ,; Numerical simulation; Secundary recovery; ENGENHARIAS::ENGENHARIA DE PETROLEO